Molecular characteristics of Staphylococcus aureus isolated from a major hospital in Lebanon - Tokajian, Sima T. (2014)
Objectives The occurrence and dissemination of methicillin-resistant Staphylococcus aureus (MRSA) in healthcare settings and the community and its risk of being introduced into hospitals are matters of great concern. The purpose of this study was to conduct a miniaturized epidemiological analysis of S. aureus-associated infections and to characterize the isolates by a variety of molecular typing techniques. Ongoing molecular surveillance is essential to prevent S. aureus strains from becoming endemic in the Lebanese healthcare setting. Methods A total of 132 S. aureus from different clinical specimens were isolated over a 6-month period. Characterization of the isolates was done by detection of the mecA gene, Panton–Valentine leukocidin determinant detection, staphylococcal chromosomal cassette (SCCmec) typing of MRSA, S. aureus protein A (spa) typing, multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), and antibiogram analysis. Results MRSA represented 30% of the isolates, with PVL being detected in 54% of MRSA and 12% of methicillin-susceptible S. aureus (MSSA). A difference between MRSA and MSSA was observed in the spa types. Clustering SCCmec with MLST identified seven MRSA and 20 MSSA clones, with PVL-positive ST80-MRSA-IV being the dominant clone (7%), while PFGE revealed 32 groups with 80% cutoff similarity. Conclusions Although the results of this study are based on samples collected from one hospital, the high diversity observed along with the lack of any equivalence in the genetic backgrounds of the major MSSA and MRSA clones, emphasizes the urgent need for standardized surveillance combined with the application of well-validated typing methods to assess the occurrence of MRSA and subsequently to control its spread.